Probiotic effects of Lactococcus lactis and Leuconostoc mesenteroides on stress and longevity in Caenorhabditis elegans - Stover, Mylissa A.; Tinoco-Bravo, Brenda; Shults, Crystal A.; Marouk, Sydney; Deole, Ratnakar; Manjarrez, Jacob R. (Frontiers in Physiology, 2023)
The Caenorhabditis elegans short lifespan enables the efficient investigation of probiotic interventions affecting stress and longevity involving the potential therapeutic value of Lactococcus lactis and Leuconostoc mesenteroides isolated from organic basil. The lactic acid bacteria were cultured from produce collected from a local grocery store in Tulsa, Oklahoma, then identified through 16S rDNA sequencing and biochemical tests. To dive deep into this analysis for potential probiotic therapy, we used fluorescent reporters that allow us to assess the differential induction of multiple stress pathways such as, oxidative stress and the cytoplasmic, endoplasmic reticulum, and the mitochondrial unfolded protein response. This is combined with classic health span measurements of survival, development, and fecundity, allowing a wide range of organismal observation of the different community of microbes supported by probiotic supplementation with Lactococcus lactis and Leuconostoc mesenteroides. These strains were initially assessed in relation to the Escherichia coli feeding strain, OP50 and the C. elegans microbiome. The supplementation showed a reduction in the median lifespan of the worms colonized with the microbiome. This was unsurprising, as negative results are common when probiotics are introduced into healthy microbiomes. To further assess the supplementation potential of these strains on an unhealthy (undifferentiated) microbiome, the typical axenic C. elegans diet, OP50, was used to simulate this single species biome. The addition of lactic acid bacteria to OP50 led to a significant improvement Probiotic effects of Lactococcus lactis and Leuconostoc mesenteroides on stress and longevity in Caenorhabditis elegans 2 in median and overall survival in simulated biomes, indicating their potential in probiotic therapy.The study analyzed the supplemented cultures in terms of C. elegans' morphology, locomotor behavior, reproduction, and stress responses, revealing unique characteristics and stress response patterns for each group. As the microbiome's influence on health span gains interest, the study aims to understand the microbiome relationships that result in differential stress resistance and lifespan by supplementing microbiomes with Lactococcus lactis and Leuconostoc mesenteroides isolated from organic basil in C. elegans.